Konseling Kejatmikaan: Integrasi Kearifan Lokal dalam Praktik Konseling di Indonesia - Alfi Kamelia Mubarok; Tazkia Aulia Az-Zahra; Lia Choirunisa; Bakhrudin All Habsy (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
Kejatmikaan counseling emerged as a unique approach to counseling practice in Indonesia, based on the teachings of Kyai Samin Surosentiko that integrates social and spiritual values. Within the context of Indonesia's cultural diversity, this counseling system aims to combine international theories with local wisdom. This research explores important elements in Kyai Samin's teachings, including self-management, social awareness, and patterns of human relationships. A hermeneutic qualitative method was used to explore the basic philosophy and key concepts underlying Kejatmikaan counseling. The findings show that this approach does not only focus on solving clients' problems, but also encourages self-development and deeper awareness, resulting in individuals behaving positively in daily life. Therefore, Kejatmikaan counseling is expected to be a model of counseling practice that is harmonious with the cultural values of the community. The results of this study include: (1) Basic philosophy, (2) Main concepts, (3) Objectives of Kejatmikaan counseling, (4) Counseling relationships, (5) Counseling techniques.